Cloud computing technologies in educational institutions - T. L. Arkhypova; T. V. Zaitseva (Academy of Cognitive and Natural Sciences, 2013)
Integration into the European educational space requires the introduction into the educational process of higher education of the latest methods based on the use of ICTs. One of the main tasks of the education system is to ensure that everyone has free and open access to knowledge, taking into account their needs, abilities, and interests. To improve the learning process, it makes sense to use powerful technologies such as "cloud computing," which, while supporting traditional forms of learning, is a new stage in the development of education and a cost-effective, efficient and flexible way to meet the needs of students to obtain new knowledge. With the help of already existing technologies and tools, it is possible to create a local "computing cloud" for the educational institution to use its resources in accordance with modern educational requirements.